Do satellite surface soil moisture observations better retain information about crop-yield variability in drought conditions? - Modanesi, S.; Massari, C.; Camici, S.; Brocca, L.; Amarnath, Giriraj (American Geophysical Union, 2020)
Soil moisture is a highly suitable indicator for assessing agricultural drought, as plants start to wilt when there is not sufficient soil water to meet evapotranspiration demand. In this study, we provide insights on information obtained from satellite surface soil moisture observations (as compared to modeled soil moisture and observed ground precipitation) on water stress and its impact on crop production variability in India. The analysis involved generating a Standardized Soil Moisture Index using (1) satellite soil moisture observations from the European Space Agency Climate Change Initiative and (2) the Modern-Era Retrospective Analysis for Research and Applications, version 2 soil moisture data set as well as producing a Standardized Precipitation Index using ground-based rainfall observations from the Indian Meteorological Department. Spanning the period from 1998 to 2015, the study covers Maharashtra and Karnataka states. These states were recently hit by a severe drought, resulting in significant crop failure and human losses. Results show that soil moisture is an important limiting factor for crop production. As such, it is more suitable for representing agricultural drought than precipitation during drought conditions, as it correlates more closely with reduced crop yields. Additionally, using the satellite-based Standardized Soil Moisture Index seemed to explain crop yield reductions better than when we applied the model-based Standardized Soil Moisture Index from Modern-Era Retrospective Analysis for Research and Applications, version 2, particularly for irrigated crops (i.e., wheat). This preliminary study can underpin future crop-forecasting tools assimilating satellite soil moisture data. In practice, satellite soil moisture may help to improve the efficiency of agricultural and irrigation management practices.